ANALISIS KESULITAN BELAJAR CHOUKAI MAHASISWA TAHUN ANGKATAN 2019 PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - fauziah putri; Meira Anggia putri (Universitas Negeri Padang, 2022)
In the Japanese language education listening skill know as choukai. but For students of the Japanese Language Education Study Program at Padang State University, there must be difficulties affecting students in terms of internal and external factors. Based on the preliminary study conducted by the researcher, it was found that there were some difficulties in learning choukai, therefore the authors decided to research and search more fully the factors that cause choukai learning difficulties.This study aims to describe the factors that cause difficulties in learning choukai at 2019 academic year students of Japanese Language Education Study Program, the type of research is descriptive quantitative. The populations of this study was amounted to 59 students. The sample of the study was the entire population using a total sampling technique, namely all students in the 2019 Japanese Language Education Study Program, Universitas Negeri Padang. The data collection technique used is a questionnaire with a likert scale. The data analysis technique used is descriptive with percentage. The result of this study were obtained factors that cause difficulties to learn listening students are, internal factors 1) the students physical condition on decline or sick, 2) students experience not used to communicating with native speakers. Exsternal factors 1) the speaking style factor, the speaker which is too fast, 2) the speaker factor that uses the hatsuon is very fast cause students have difficulty getting informasion.